The rise of authoritarianism in a democratic regime in Aristophanes’ Assemblywomen - Drumond, Greice (Revista Conexão Letras, 2021)
The plot of Assemblywomen tells the story of a coup organized by a group of women to conquer power and administrate the city of Athens. By examining the historical and dramatic elements in this comedy, we seek to comprehend the use of the notions of liberty and democracy, taking into consideration that through the drama we glimpse on what can happen when democracy is undermined. Aristophanes made use of artistic liberty to redefine the parameters of his art, showing a new form of comedy and how liberty can contribute to the development of art and society.